Enviromental impact created by plastic bottles - Sawicka, Jessica (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
Plastic bottles provide functionality, convenience and efficiency at a cost to the environment. These bottles end up in landfills or the ocean if not recycled. Legislation aims at tackling this problem by implementing Bottle Bills that provide economic incentive for returning bottles for either a deposit, tax or fee. Moreover, producers are expected to improve the design of bottles to ease recycling. However, requiring manufactures to market drinks in only reusable containers is deemed as going too far and interfering with the free market economy. Yet, the legislature does take interest in promoting resource conservation and resolving waste disposal issues. The solution could be by providing access to safe drinking water points thought the city so that residents can refill their reusable bottle. An issue arises when the water network breaks and leaves a city to function solely on plastic bottles. Therefore, it is important to implement water purification technology into daily life to prevent such a crisis.
Keywords: plastic bottles; the European Strategy for Plastics in a circular Economy; environmental protection; environment